Analysis of Sumur Deringo Stories in Sumuranja Selatan Village for Elementary School Children - Mirna Sukoyati (Mitra Palupi, 2023)
Background: Folklore is cultural literature that is passed down by word of mouth to be passed down from generation to generation to the next generation. However, there are many generations today who are not aware of the existence of folklore or storytelling, even though there is a lot of learning involved. Purpose: The purpose of this research is to find out the story of Sum Ringo in the village of South Sumuranja as well as to analyze the intrinsic and extrinsic elements contained in the story of Sum Ringo for elementary school children. Design and methods: The method used in this research is ethnographic method with a qualitative approach. Data collection techniques in this ethnographic method are through interviews, observation and documentation. Results: The results of the study show that the story of Sum Ringo is a story formed from an activity carried out by the community. The story has indeed been trusted by the surrounding community which has been passed down by word of mouth from generation to generation to the next generation. Likewise, some elementary school children already know the story. The story contains lessons for children. From the results of the analysis, the story contains intrinsic elements consisting of themes, plot, characters and characterizations, setting, point of view and message, as well as other elements. external which consists of the cultural background and moral values ​​contained in the story.